Edukasi Pencegahan Penularan Covid-19 dan Pembelajaran Matematika Bagi Siswa SD Kelas IV di Hante-hante, Desa Salumokanan Utara, Rantebulahan Timur, Mamasa - Defi Lestari -; Andi Sadapotto (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
Public awareness that is still lacking on the importance of complying with health protocols such as washing hands, wearing masks, and maintaining distance is the basis for selecting the topic of education on the prevention of Covid-19 transmission in the 105th batch of Hasanuddin University Real Work Lecture (KKN) located in Hante-hante, Salumokanan Village. Utara, Rantebulahan Timur District, Mamasa Regency, West Sulawesi. Through the distribution of hand soap and masks to residents around the house, making handwashing stations along with posters for proper and correct hand washing in front of the Toraja Mamasa Church building in the Hante-hante Congregation and in front of the house as pilot materials, as well as making pamphlets on the prevention of Covid- 19 which were shared via social media (WhatsApp). In addition, the impact of the Covid-19 pandemic on the education sector, namely regarding the policy of the online teaching and learning system, has made learning in North Salumokanan Village not able to be implemented optimally, considering that the main supporting facilities for the internet network cannot be fully accessed. In addition, the economic level of the community belonging to the middle to lower economic community is not possible to have other supporting facilities such as cellphones, laptops, etc. So, the authors took the initiative to provide additional lessons related to scientific fields, in this case, mathematics lessons targeting students at the fourth grade level of elementary school who live around the house. The results obtained from the implementation of this work program are that the public can be reminded again to adhere to health protocols in order to break the chain of Covid-19 spread, while in terms of learning there is an increase in student knowledge and understanding regarding the concepts of fractions and multiplication.